Menstrual territories: corporeal cartography as a methodological tool in critical menstrual studies and feminist geographies - Morón-Tadic, Kathya Milena; De-la-Fuente-Véliz, Sofía (Investigaciones Geográficas, 2023)
Considering the menstrual experience as a phenomenon intersected by gender and impacting multiple dimensions in the lives of those who cycle, it appears crucial to experiment with methodologies that allow for the visualization and mobilization of the affective and corporeal dimensions of this experience. Thus, we seek to create spaces where we engage in the practice of body mapping from perspectives that appeal to the spatialization of bodies, self-enunciation, and the production of situated knowledge. In this article, we present some of the theoretical and methodological reflections that have emerged from the exploration of this exercise within the framework of the Territorios menstruales project, in which both authors participate. Referring to the menstrual body mapping workshops we have conducted, we emphasize on the relevance of body mapping as a tool in the fields of critical menstrual studies and feminist geographies. The primary contribution of this article is therefore methodological, as we envision that, in addition to generating knowledge regarding how individuals signify their menstrual cycle through visual methodologies that connect experience, bodies, and territories, a tool for self-awareness, agency, and social transformation will be disseminated.